AUTHORITY OF THE BUSINESS COMPETITION SUPERVISORY COMMISSION (KPPU) IN CASE MANAGEMENT COMPETITION (STUDIES COMPARATIVE IN INDONESIA BY COMMON LAW SYSTEM COUNTRIES) - Sapitri, Baiq Ervinna (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
Each state is required to have regulations governing the activities of the market and establish a special commission to oversee and prevent unhealthy competition, such as in Indonesia with the Act No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Competition, in the form of a special commission that is KPPU. The Commission is authorized to conduct research and investigations, but the Commission does not have the authority to conduct a search on their own. Different than the institutions like in some common law countries have independent authority conducting the search.Keywords: Authority, KPPU, Common Law Countries